(untitled) (Journal of the College of Basic Education, 2022)
The continuous wars in Andalusia during the era of the kings of the sects had a clear impact on the emergence of poetry. The weapon that depicts the wars that the Muslims fought against the Christians, and the weapons that they used to fight. They use them in battle and the importance of each type, and to stand up to their sweeping schemes, which are trying hard to eliminate Islam and the Muslims in Andalusia, so the poets started praising their victory to encourage the Muslims And mobilizing their determination, the poetry of arms took a wide place in their poetry, and entered most of their purposes. Poetic praise, pride, lamentation and spinning, and praise was most of these purposes related to the description of the weapon.